Representation of al-Madâih al-Nabawiyyah Kasidah al-Barzanji: Literary Analysis and Tawhîd Theory of Genetic Structuralism - Tamam, Asep M.; Rohanda, Rohanda; Supardi, Adi; Hazim, Hana; Hermawan, Acep (Arabi : Journal of Arabic Studies, 2025)
This study aims to examine the representation of literature and tawḥīd in al-mada’iḥ al-nabawiyyah kasidah al-Barzanji. The existence of al-mada’iḥ al-nabawiyyah has become popular and attracted the attention of the Muslim community worldwide, along with the attention of Muslims who consider al-mada’iḥ al-nabawiyyah kasidah al-Barzanji as a beneficial form of worship. This study employs a descriptive qualitative method with a genetic structuralism theoretical approach. Data analysis involves literature review from relevant sources, with primary data obtained from the al-Barzanji text. The findings reveal that the al-mada’iḥ al-nabawiyyah kasidah contains literary and tawḥidic elements that are beneficial. From a literary perspective, the al-Barzanji kasidah possesses intrinsic elements such as plot, setting, characterization, style, and theme. These findings are highly beneficial in enhancing readers' understanding and appreciation. Meanwhile, the findings on tawḥīd reveal that there are nine verses in the al-Barzanji kasidah containing tawhīd ulūhiyyah and rubūbiyyah, aimed at fostering the religious quality of Muslims.